Anatomy of Customary Institutions and Social Resilience: Structural Functionalism Analysis (AGIL) on the Baduy Tribe's Government System - Usman Supendi; Mulyanudin Mulyanudin; Yusandi Yusandi; Abdul Aziz; Hafizh Fadlan (MASI Mandiri Edukasi, 2026)
The Baduy (Kanekes) indigenous community in Banten, Indonesia, represents a distinctive sociological case of social resilience amid increasing modernization and state intervention. Previous studies have primarily focused on cultural traditions, ecological wisdom, and ritual practices, while paying limited attention to how customary institutions function as an integrated governance system that supports social resilience. This study aims to analyze the anatomy of Baduy customary institutions and examine their roles in maintaining social resilience through Talcott Parsons’ AGIL framework. A qualitative descriptive case study was conducted using secondary data obtained from ethnographic monographs, journal articles, government documents, cultural heritage publications, and sociological studies. Data were collected through literature review and document analysis, then analyzed using thematic coding and AGIL-based classification procedures. The findings indicate that Baduy customary governance consists of interdependent institutions that perform complementary functions related to adaptation, goal attainment, integration, and cultural maintenance. The analysis suggests that institutional differentiation and functional interdependence support the preservation of cultural values while facilitating engagement with external administrative and political systems. The study extends the application of the AGIL framework to indigenous governance and provides insights for cultural preservation, indigenous governance recognition, and state–customary relations in contemporary society.